2021
DOI: 10.17267/2238-2704rpf.v11i4.4087
|View full text |Cite
|
Sign up to set email alerts
|

Perceived barriers to physical activity among Malaysian adults during COVID-19 pandemic- a cross-sectional study

Abstract: INTRODUCTION: The COVID-19 pandemic has brought a relatively significant impact on the world. Malaysia implemented a countrywide social isolation strategy to flatten the epidemic curve. As limits on movement and social interaction have come into force, more individuals appear less physically active. OBJECTIVE: To determine the perceived barriers to physical activity among Malaysian young adults during the Covid-19 Pandemic. METHODS AND MATERIALS: Total 217 participants included with age group from 18-40 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(12 reference statements)
0
0
0
Order By: Relevance
“…In the answers given by the students to the items in the personal subdimension of the scale, it was concluded that they did not have enough energy for physical activity, the activity was difficult and tiring, they were afraid of being injured, and they could not maintain their self-discipline. Yao et al (2021), Ibrahim et al (2013 support the findings of their research.…”
Section: Discussionmentioning
confidence: 64%
“…In the answers given by the students to the items in the personal subdimension of the scale, it was concluded that they did not have enough energy for physical activity, the activity was difficult and tiring, they were afraid of being injured, and they could not maintain their self-discipline. Yao et al (2021), Ibrahim et al (2013 support the findings of their research.…”
Section: Discussionmentioning
confidence: 64%